Cloud-based Engineering Design and Manufacturing: State-of-the-Art - Tarchinskaya, Ekaterina; Taratoukhine, Victor; Matzner, Martin (Proceedings of the 2013 IFAC Conference on Manufacturing, Modelling, Management, and Control (IFAC MIM 2013), 2013)
Cloud-based technologies proliferated in the past few years, while the manufacturing industry moved towards digitization and network. Therefore, cloud-based technologies have been adopted in the development of new generation manufacturing systems which orchestrate different activities, including product design, process and task planning, production, customer service, etc. These new cloud-ingrained technologies have the potential to change the collaboration of product development partners, the processing and sharing of information as well as utilizationrates of critical equipment. Cloud-based technologies affect many aspects of manufacturing activities, and they therefore have the power to enable new or change existing business models of the manufacturing industry. Based on the literature review, this paper analyzes the latest requirements, challenges, and trends of the manufacturing industry. It structures the findings in a coherent manner and further hypothesizes how cloud computing may address identifed requirements and challenges as well as realize or support new concepts in manufacturing.
Keywords: Manufacturing; engineering design; cloud computing; agile manufacturing; business processes